Urinary mRNA and lupus disease flare. (20th November 2017) - Szeto, Cheuk‐Chun
Summary at a Glance: We review the published evidence for the use of urinary mRNA level for risk stratification and prediction of disease flare in patients with lupus nephritis. ABSTRACT: In the past 20 years, extraction and quantification of mRNA from urinary sediment has emerged as a novel laboratory technique. The potential application of urinary mRNA quantification to the clinical care of patients with SLE has become an active field of research. However, published studies in this area are limited to small‐scale ones. mRNA levels of several of cytokine and transcript factor genes have been found to have the potential for the diagnosis or monitoring of disease activity in patients with lupus nephritis. Our previous studies showed that a high urinary mRNA level of T‐bet, the key transcription factor of type 1 T helper cells (Th1), was an independent predictor of lupus flare and probably reflects an intrinsic characteristic of patients with predisposition to Th1 activation. Other studies suggest that monitoring of monocyte chemoattractant protein‐1(MCP‐1), interleukin (IL)‐17, GATA‐3 (the key transcription factor of type 2 T helper cells) and forkhead box P3 (FOXP3, the key transcription factor of regulatory T cells) mRNA level in urinary sediment may provide an early clue for detecting disease flare in lupus patients. As a simple and non‐invasive method, urinary mRNA level deserves further studies to validate its role in risk stratification and monitoring of patients with lupus nephritis.